1993
DOI: 10.1021/bi00080a005
|View full text |Cite
|
Sign up to set email alerts
|

X-ray scattering using synchrotron radiation shows nitrite reductase from Achromobacter xylosoxidans to be a trimer in solution

Abstract: We demonstrate here the applicability of X-ray scattering for studying molecular conformation of multimeric proteins in solution by using synchrotron radiation to extend the range of data collection to include medium angles (ca. 3-4 degrees). We have been able to define the solution structure of the dissimilatory nitrite reductase of Achromobacter xylosoxidans (AxNiR), an enzyme for which there are conflicting reports as to the nature of its multimeric structure. Quantitative interpretation of the X-ray scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
34
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 19 publications
10
34
1
Order By: Relevance
“…The values in Table 1 show that for all three types of scattering the calculated profile is significantly closer to experiment when the solvent molecules are explicitly included. This result confirms previous studies indicating that it is necessary to take into account hydration effects in SAS studies (15,33,34). Fig.…”
Section: Resultssupporting
confidence: 92%
“…The values in Table 1 show that for all three types of scattering the calculated profile is significantly closer to experiment when the solvent molecules are explicitly included. This result confirms previous studies indicating that it is necessary to take into account hydration effects in SAS studies (15,33,34). Fig.…”
Section: Resultssupporting
confidence: 92%
“…This results in a signi®cant loss of ®xed nitrogen from the terrestrial environment (Payne, 1985;Zumft, 1997) Two types of NiRs are found in the denitrifying bacteria, the cytochrome cd 1 and copper NiRs (CuNiR); the latter are more widespread, being found in bacteria occupying a greater variety of habitats. The trimeric structures of several CuNiRs have now been established by X-ray crystallography [Achromobacter cyoclastes (AcNiR; Godden et al, 1991); Alcaligenes faecalis S-6 (AfNiR; Kukimoto et al, 1994) and Alcaligenes xylosoxidans (AxNiR; Dodd et al, 1998)] and solution X-ray scattering [AxNiR (Grossmann et al, 1993), Pseudomonas aureofaciens (PaNiR) and AfNiR (Grossmann & Hasnain, 1997)]. The crystal structures of the three CuNiRs show that they are similar, with the monomer consisting of two domains with Greek key -barrels similar to those found in cupredoxins.…”
Section: Introductionmentioning
confidence: 99%
“…NCIMB 11015, Achromobacter xylosoxidans or Pseudomonas denitri®cans), the reduction of nitrite to nitric oxide is accomplished by a copper-containing nitrite reductase Grossmann et al, 1993;Strange et al, 1995). Two classes of blue copper proteins, pseudoazurin and azurin, have so far been implicated in donating electrons to nitrite reductase; pseudoazurin to the green nitrite reductases of A. faecalis S-6 and Achrom.…”
Section: Introductionmentioning
confidence: 99%